The big sombrero - McDonald, Frank, 1899-1980; Autry, Gene, 1907-1998; Verdugo, Elena, 1926-; Gene Autry Productions; Cinetel Films ([Hollywood, CA] : Gene Autry Productions, 1949)
Gene is hired to be foreman of the Big Sombrero ranch by Jim Garland, who is handling all the business affairs of the owner, Estrellita Estrada, who is more interested in going to America than taking care of her Mexican holdings. Gene, discovering Garland's plan to run all the Mexican rancheros off the ranch, turns against his boss and shortly finds himself in the middle of cattle stampedes and an avalanche started by Garland's men. --
Gene Autry, Champion, Elena Verdugo, Stephen Dunne, George J. Lewis, Vera Marshe, William Edmunds, Martin Garralaga, Gene Stutenroth, Neyle Morrow.
Cinematographer, William Bradford ; editor, Henry Batista; music, Mischa Bakaleinikoff; Joseph Dubin.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Ranchers -- Drama; Mexico -- Drama; Old-time music; Western films; Feature films; Internet videos; Streaming video